Sosialisasi Inovasi Pembuatan Kerupuk Ikan Wader Sebagai Upaya Pengembangan Produk Komoditas Perikanan - Zahra Fayza Azzahra; Verio Rinaldo Soegianto; Muchammad Zidane Albarra; Kania Laras Puspitasari; Bian Ade Anggita; Erminah Dwi Ambarwati; Angelia Fortunata Arisman; Karina Danti Aulia Rahma; Salman Akbar; Devi Dwi Anggraini (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The 2024 State Defense Thematic Real Work Lecture (KKNT) has been held in 9 villages in Trowulan District, one of which is Trowulan Village. The village has culinary delights that utilize fishery commodities, namely Wader Fish, so students want to create processed products with added value and a long shelf life. Apart from that, students also teach the community about the use and conservation of resources. Community service carried out by students through product development innovation uses two qualitative methods with exposure and practice. The data collection techniques used are observation, interviews, and documentation. In general, the fishery commodity that is often used is wader fish which is used as a fried fish with sambal by the community. However, its shelf life is fast so it doesn't last long. Therefore, students created a product development program through food diversification in the form of Wader Crackers. Wader Crackers are a solution to supply protein, carbohydrates, calcium and other nutrients as well as supporting the preservation of the environment and local culture in the use of superior food commodities in local villages.